An Optimized Video Steganographic Method based on Ant Colony Optimization (ACO) Algorithm - Raja, SP.Prabu; Mahesh, K. (IJRDO -Journal of Computer Science Engineering, 2017)
With the development of multimedia application, there is preserving the privacy of information from imposters is increasingly important much. In the area of information hiding, “Steganography” means “covered writing” which is prominent technique to hide the sensitive information inside another medium. In Steganography, various stego objects are used for hiding purpose but the video is to be consider as more efficient than other objects due to separation of image and audio and also it has capability to hide the large voluminous of confidential data. Video Steganography defines hide the information inside the cover object called stego video. Among different transform domain methods, IWT is effective than other due to its efficacy. The aim of the proposed research work is to find best values using ACO (Ant Colony Optimization Algorithm) and the secret information is embedded in those values to obtain the stego video. In this proposed scheme, IWT is adopted to get the transformation coefficients; on these coefficients, ACO algorithm is applied to obtain the optimal values to conceal the data. This developed steganographic scheme is convenient for embedding / extracting of massive amount of data from/into the stego video. Experiments are carried out on several test videos; results demonstrated that best quality in visual, high security and also embedding huge data